Laboratory bioassay of some entomopathogenic fungi against broad mite (Polyphagotarsonemus latus Bank) - Nugroho, Ihsan; Ibrahim, Yusof (Friends Science Publishers, 2004)
Laboratory bioassay of three entomopathogenic fungi Beauveria bassiana (Bals.) Vuill., Metarhizium anisopliae (Metch.) Sorokin, Paecilomyces fumosoroseus (Wise) Brown & Smith against broad mite (Polyphagotarsonemus latus Bank) was evaluated. Effect of these fungi on the broad mite egg was also investigated. Dose mortality bioassay revealed that B. bassiana (Glenia celiaisolate, BbGc) caused mortality up to 80.88% at a dose 1 x 108 conidia mL-1 while M. anisopliae (Phylotreta striolata isolate, MaPs) and P. fumosoroseus (Pteroma pendula isolate, PfPp) caused 60 and 90% mortality, respectively. Significant relationship (P=0.05) was obtained between log concentration and probit mortality value for all the three isolates. The effective concentration of B. bassiana to kill 50% mite treated (EC50) was the lowest (2.74 x 106 conidia mL-1) followed by that of P. fumosoroseus (3.23 x 106 conidia mL-1) and M. anisopliae (2.77 x 107 conidia mL-1). The LT50 at comparable dosage (1 x 108 conidia mL-1) of B. bassiana, M. anisopliae and P. fumosoroseus were 3.4 (1.4 - 5.1), 4.3 (3.3 – 5.8) and 2.8 (1.9 – 3.9) days, respectively. Therefore B. bassiana proved to be the most effective followed by P. fumosoroseus and M. anisopliae. However P. fumosoroseus caused mortality more quickly than others. There was poor infection on the mite eggs (10%) caused by M. anisopliae while no infection was recorded by B. bassiana and P. fumosoroseus.